Associations between problematic Internet use and psychiatric symptoms among university students in Japan. Issue 7 (9th May 2018) - Kitazawa, Momoko; Yoshimura, Michitaka; Murata, Mayu; Sato‐Fujimoto, Yuka; Hitokoto, Hidefumi; Mimura, Masaru; Tsubota, Kazuo; Kishimoto, Taishiro
Abstract : Aim: Research on the adverse effects of Internet use has gained importance recently. However, there is currently insufficient data on Japanese young adults' Internet use, so we conducted a survey targeting Japanese university students to research problematic Internet use (PIU). We also investigated the relationship between PIU and multiple psychiatric symptoms. Methods: A paper‐based survey was conducted at five universities in Japan. Respondents were asked to fill out self‐report scales regarding their Internet dependency using the Internet Addiction Test (IAT). Sleep quality, attention‐deficit hyperactivity disorder (ADHD) tendency, depression, and anxiety symptom data were also collected based on respective self‐reports. Results: There were 1336 responses and 1258 were included in the analysis. The mean IAT score (± SD) was 37.87 ± 12.59; and 38.2% of participants were classified as PIU, and 61.8% as non‐PIU. The trend level for young women showed that they were more likely to be classified as PIU than young men (40.6% and 35.2% respectively, P  = 0.05). Compared to the non‐PIU group, the PIU group used the Internet longer ( P  < 0.001), had significantly lower sleep quality ( P  < 0.001), had stronger ADHD tendencies ( P  < 0.001), had higher Depression scores ( P  < 0.001), and had higher Trait‐Anxiety scores ( P  < 0.001). Based on multiple logistic regression analyses, the factors that contributed to an increased risk of PIU were: being female (odds ratio [OR] = 1.52), being older (OR = 1.17), having poor sleep quality (OR = 1.52), having ADHD tendencies (OR = 2.70), having depression (OR = 2.24), and having anxiety tendencies (OR = 1.43). Conclusion: We found a high PIU prevalence among Japanese young adults. The factors that predicted PIU were: female sex, older age, poor sleep quality, ADHD tendencies, depression, and anxiety.